Purification method of 2, 5-furandicarboxylic acid
By using a selective hydrogenation catalyst supported by a nitrogen-doped nanocarbon cage in organic solvent and water, the difficult-to-removal 5-formyl-furan-2-formic acid in 2,5-furandiformic acid is converted into easily removed 5-hydroxymethyl-furan-2-formic acid, which is solved in the prior art, the problems of high purification cost and low recovery rate of 2,5-furandiformic acid in the prior art are solved, and the purification effect of high purity and high recovery rate is achieved.
Patent Information
- Application Number
- CN202311086533.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-28
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2043-08-28
AI Technical Summary
In the prior art, 2,5-furandicarboxylic acid has high purification cost, 5-formyl-furan-2-formic acid impurities are difficult to remove, and the recovery rate is low.
A hydrogenation reaction is carried out by contacting a 2,5-furandicarboxylic acid raw material containing 5-formyl-furan-2-formic acid impurity in the presence of an organic solvent and water. The catalyst includes support nitrogen-doped nanocarbon cage-supported Pd, which converts 5-formyl-furan-2-formic acid into easily removed 5-hydroxymethyl-furan-2-formic acid by hydrogenation reaction.
It has achieved efficient purification of 2,5-furandicarboxylic acid, with product purity reaching more than 99%, recovery rate exceeding 90%, and treatment cost is reduced.
Smart Images

Figure CN119552139A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of chemical industry, and in particular to a method for purifying 2,5-furandicarboxylic acid. Background Art
[0002] Generally speaking, 2,5-furandicarboxylic acid (FDCA) synthesized from biomass resources has a similar structure to terephthalic acid and is easily degraded in nature. It is mainly used to synthesize high-performance degradable polymers such as polyester, nylon, and epoxy resin. In particular, polyethylene 2,5-furandicarboxylate (PEF) obtained by the polymerization of 2,5-furandicarboxylic acid and ethylene glycol has better mechanical and thermal properties and better gas barrier properties than polyethylene terephthalate (PET).
[0003] At present, the main by-products in the production process of 2,5-furandicarboxylic acid include 2,5-diformylfuran (DFF), 5-hydroxymethyl-furan-2-carboxylic acid (HFCA), 5-formyl-furan-2-carboxylic acid (FFCA), etc. Among them, since the solubility of 5-formyl-furan-2-carboxylic acid in various solvents is very close to that of 2,5-furandicarboxylic acid, it is an impurity that is difficult to remove in the crude 2,5-furandicarboxylic acid, resulting in low purity of 2,5-furandicarboxylic acid and adverse effects on the polymerization reaction of 2,5-furandicarboxylic acid.
[0004] Chinese patent application CN103965146A discloses a method for purifying furandicarboxylic acid, which uses a salt-forming reaction to filter, acidify, and precipitate a solid from an aqueous solution of furandicarboxylic acid, and then wash and dry to obtain a product, and a pre-purification process is added to treat low-purity furandicarboxylic acid raw materials. Due to the salt-forming reaction involved, the method will produce a large amount of salt-containing acidic wastewater in the acidification step, causing great environmental pressure, and the acyl-containing substances in the furandicarboxylic acid product obtained by the method cannot be completely removed, and their presence will cause the product to turn yellow, which will have a certain impact on the subsequent polymerization reaction.
[0005] Chinese patent application CN113121480A provides a method for purifying and refining 2,5-furandicarboxylic acid by using a melt crystallization method, which requires the material to be heated to above 290°C, has high energy consumption, and has high requirements for equipment. Chinese patent application CN110713474A provides a method for refining furan dicarboxylic acid by using a dissolution crystallization method, which involves the use and removal of a large amount of high-boiling point solvents, and also increases energy consumption and the complexity of the method. Therefore, how to improve the purity of 2,5-furandicarboxylic acid is a problem that people in this field need to further solve. Summary of the invention
[0006] The purpose of the present invention is to overcome the problems of high purification cost of 2,5-furandicarboxylic acid, great difficulty in removing 5-formyl-furan-2-carboxylic acid impurities and low recovery rate of 2,5-furandicarboxylic acid in the prior art, and to provide a method for purifying 2,5-furandicarboxylic acid, which has good purification effect, low processing cost and can obtain a higher recovery rate of 2,5-furandicarboxylic acid.
[0007] In order to achieve the above object, the present invention provides a method for purifying 2,5-furandicarboxylic acid, wherein the method comprises the following steps:
[0008] (1) contacting a 2,5-furandicarboxylic acid raw material containing 5-formyl-furan-2-carboxylic acid impurity, hydrogen and a selective hydrogenation catalyst in the presence of an organic solvent and water to carry out a hydrogenation reaction;
[0009] (2) subjecting the product obtained in step (1) to solid-liquid separation and washing;
[0010] The catalyst comprises a carrier and an active metal component Pd loaded on the carrier, wherein the content of Pd is 0.1-2 mass %; the carrier is a nitrogen-doped nanocarbon cage; the nitrogen-doped nanocarbon cage has a hollow cage-like structure, and the BET specific surface area of the nitrogen-doped nanocarbon cage is 400-1000 m 2 / g; the pore size of the nitrogen-doped nanocarbon cage is 2-50nm; based on the total molar amount of nitrogen, the molar content of pyrrolic nitrogen and / or pyridinic nitrogen in the nitrogen on the surface of the nitrogen-doped nanocarbon cage measured by X-ray photoelectron spectroscopy is greater than 85%.
[0011] The inventors of the present invention have found in their research that the solubility of 5-hydroxymethyl-furan-2-carboxylic acid in water is significantly higher than that of 2,5-furandicarboxylic acid and 5-formyl-furan-2-carboxylic acid. After 5-formyl-furan-2-carboxylic acid is hydrogenated to 5-hydroxymethyl-furan-2-carboxylic acid with high selectivity, the impurity can be removed by water washing. Therefore, how to efficiently achieve the selective hydrogenation of a small amount of 5-formyl-furan-2-carboxylic acid impurities in crude 2,5-furandicarboxylic acid is of great significance.
[0012] The present invention unexpectedly found that in the hydrogenation reaction of 5-formyl-furan-2-carboxylic acid, a selective hydrogenation catalyst using a nitrogen-doped nanocarbon cage with a hollow cage-like structure and a high specific surface area as a carrier to load Pd is used in conjunction with the method and reaction conditions of the present invention, that is, a small amount of 5-formyl-furan-2-carboxylic acid can be hydrogenated to 5-hydroxymethyl-furan-2-carboxylic acid while limiting the hydrogenation conversion of 2,5-furandicarboxylic acid, thereby providing a basis for the subsequent removal of impurities and purification of the 2,5-furandicarboxylic acid product.
[0013] The purification method provided by the present invention can efficiently convert 5-formyl-furan-2-carboxylic acid impurities that are difficult to remove by other methods into easily removable 5-hydroxymethyl-furan-2-carboxylic acid under relatively mild conditions, thereby removing impurities by simple water washing, and significantly improving the product purity of 2,5-furandicarboxylic acid. For example, the recovery rate of 2,5-furandicarboxylic acid in the embodiment is greater than 90%; in the purified 2,5-furandicarboxylic acid product, the content of 2,5-furandicarboxylic acid is greater than 99%. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 is a TEM image of the nitrogen-doped nanocarbon cage prepared in Preparation Example 1;
[0015] Figure 2 is the XPS image of the nitrogen-doped nanocarbon cage prepared in Preparation Example 1;
[0016] Figure 3 is the N1s peak spectrum of the XPS of the nitrogen-doped nanocarbon cage prepared in Preparation Example 1;
[0017] Figure 4 is the BJH pore size distribution curve of the nitrogen-doped nanocarbon cage prepared in Preparation Example 1;
[0018] Figure 5 This is the N1s peak spectrum of the XPS of the nitrogen-doped nanocarbon cage prepared in Preparation Example 2;
[0019] Figure 6 This is the N1s peak spectrum of the XPS of the nitrogen-doped nanocarbon cage prepared in Preparation Example 3. DETAILED DESCRIPTION
[0020] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0021] In the present invention, the content of Pd in the catalyst is calculated by the feed amount.
[0022] In the present invention, the nitrogen-doped nanocarbon cage has a hollow cage-like structure, and “the hollow cage-like” refers to a hollow sphere or quasi-sphere formed by being surrounded by a graphitized carbon layer.
[0023] In the present invention, the surface morphology of the material is characterized by high-resolution transmission electron microscopy (HRTEM), the model of the high-resolution transmission electron microscope used is JEM-2100 (Japan Electron Co., Ltd.), and the high-resolution transmission electron microscope test conditions are: the acceleration voltage is 200kV. The diameter of the nitrogen-doped nanocarbon cage can be measured by the high-resolution transmission electron microscope image.
[0024] In the present invention, the "nitrogen" in the term "nitrogen-doped nanocarbon cage" refers to the nitrogen element, and the term specifically refers to the nitrogen element in various forms formed in the nitrogen-doped nanocarbon cage during the preparation process of the nitrogen-doped nanocarbon cage.
[0025] In the present invention, the terms "pyrrolic nitrogen", "pyridinic nitrogen", "graphitic nitrogen" and "oxidized nitrogen" have conventional meanings in the art, specifically referring to: pyridinic nitrogen is a nitrogen species determined by a characteristic peak corresponding to a binding energy of 398.7-399.1 eV in an X-ray photoelectron spectrum; pyrrolic nitrogen is a nitrogen species determined by a characteristic peak corresponding to a binding energy of 398.8-400.2 eV in an X-ray photoelectron spectrum; graphitic nitrogen is a nitrogen species determined by a characteristic peak corresponding to a binding energy of 401.2-409.8 eV in an X-ray photoelectron spectrum; and oxidized nitrogen is a nitrogen species determined by a characteristic peak corresponding to a binding energy of 402.8-403.6 eV in an X-ray photoelectron spectrum.
[0026] In the present invention, the X-ray photoelectron spectroscopy analysis was tested on an ESCALab250 X-ray photoelectron spectrometer equipped with ThermoAvantage V5.926 software from Thermo Scientific. The excitation source was monochromatic AlKα X-ray with an energy of 1486.6 eV and a power of 150 W. The penetration energy used for narrow scanning was 30 eV. The basic vacuum during the analysis test was 6.53×10 -9 The electron binding energy was calibrated with the C1s peak (284.6 eV) of elemental carbon. The data were processed on Thermo Avantage software, and the sensitivity factor method was used for quantitative analysis in the analysis module.
[0027] In the present invention, the graphitization degree of nitrogen-doped nanocarbon cages is characterized by Raman spectroscopy. The peak at 1355 cm-1 (D peak) is attributed to structural defects and is amorphous carbon, and the peak at 1585 cm-1 (D peak) is attributed to structural defects and is amorphous carbon. -1 The peak (G peak) is attributed to the carbon in the planar structure. Usually I D / I G (D peak and G peak intensity ratio) to characterize the degree of graphitization of the material. D / I GThe higher the value, the more defects there are and the lower the degree of graphitization. The Raman spectrum of the material is obtained using a RM2000 micro-confocal Raman spectrometer (product of Reinshaw Company), and the technical indicators are: the excitation source is a He-Ne laser with a wavelength of 525nm.
[0028] The present invention provides a method for purifying 2,5-furandicarboxylic acid, wherein the method comprises the following steps:
[0029] (1) contacting a 2,5-furandicarboxylic acid raw material containing 5-formyl-furan-2-carboxylic acid impurity, hydrogen and a selective hydrogenation catalyst in the presence of an organic solvent and water to carry out a hydrogenation reaction;
[0030] (2) subjecting the product obtained in step (1) to solid-liquid separation and washing;
[0031] The selective hydrogenation catalyst comprises a carrier and an active metal component Pd loaded on the carrier, wherein the content of Pd is 0.1-2 mass %; the carrier is a nitrogen-doped nanocarbon cage; the nitrogen-doped nanocarbon cage has a hollow cage-like structure, and the BET specific surface area of the nitrogen-doped nanocarbon cage is 400-1000 m 2 / g; the pore size of the nitrogen-doped nanocarbon cage is 2-50nm; based on the total molar amount of nitrogen, the molar content of pyrrolic nitrogen and / or pyridinic nitrogen in the nitrogen on the surface of the nitrogen-doped nanocarbon cage measured by X-ray photoelectron spectroscopy is greater than 85%.
[0032] The purification method provided by the present invention can highly selectively hydrogenate 5-formyl-furan-2-carboxylic acid to 5-hydroxymethyl-furan-2-carboxylic acid through the hydrogenation reaction in step (1), and then remove 5-hydroxymethyl-furan-2-carboxylic acid through solid-liquid separation and washing, thereby obtaining a purified 2,5-furandicarboxylic acid product.
[0033] The purification method provided by the present invention uses an organic solvent and water as a mixed solvent in the hydrogenation reaction of 5-formyl-furan-2-carboxylic acid to improve the solubility of 2,5-furandicarboxylic acid and 5-formyl-furan-2-carboxylic acid in the solvent, so that 5-formyl-furan-2-carboxylic acid is uniformly dissolved in the solvent and can fully contact with a selective hydrogenation catalyst and hydrogen, so as to be reduced to 5-hydroxymethyl-furan-2-carboxylic acid with better water solubility.
[0034] In the present invention, there is no particular limitation on the source of the 2,5-furandicarboxylic acid raw material, and the method can be applied to any 2,5-furandicarboxylic acid raw material containing 5-formyl-furan-2-carboxylic acid impurities obtained by any conventional method. Preferably, the 2,5-furandicarboxylic acid raw material containing 5-formyl-furan-2-carboxylic acid impurities is selected from the crude product obtained when 2,5-furandicarboxylic acid is produced by 5-hydroxymethylfurfural oxidation. In the present invention, in order to better illustrate that the purification method of the present invention has an excellent purification effect, a 2,5-furandicarboxylic acid raw material containing impurities can be prepared and used as a simulated crude product. Preferably, 2,5-furandicarboxylic acid is mixed with 5-formyl-furan-2-carboxylic acid (preferably mechanically mixed) to obtain a 2,5-furandicarboxylic acid raw material containing 5-formyl-furan-2-carboxylic acid impurities.
[0035] In the present invention, the selection range for the content of 5-formyl-furan-2-carboxylic acid impurity is relatively wide. Preferably, in step (1), based on the total amount of 2,5-furandicarboxylic acid raw material containing 5-formyl-furan-2-carboxylic acid impurity, the content of 5-formyl-furan-2-carboxylic acid impurity is 0.1-20% by mass, more preferably 0.2-15% by mass, and even more preferably 0.5-10% by mass.
[0036] In the present invention, the contents of various components in the 2,5-furandicarboxylic acid raw material containing 5-formyl-furan-2-carboxylic acid impurity are measured by high performance liquid chromatography (HPLC).
[0037] It is known to those skilled in the art that the main by-products in the 2,5-furandicarboxylic acid raw material obtained by the conventional 2,5-furandicarboxylic acid production method may include 2,5-diformylfuran (DFF), 5-hydroxymethyl-furan-2-carboxylic acid (HFCA), etc. in addition to 5-formyl-furan-2-carboxylic acid (FFCA). The 2,5-furandicarboxylic acid raw material used in the present invention may contain the above-mentioned other by-products. When the above-mentioned by-products are contained, each by-product can be further removed by means known in the prior art.
[0038] In the present invention, preferably, in step (1), the organic solvent is selected from at least one of tetrahydrofuran, 1,4-dioxane and ethylene glycol dimethyl ether, and more preferably 1,4-dioxane. Using a mixed solution of the above organic solvent and water as a solvent helps to improve the solubility of 2,5-furandicarboxylic acid and 5-formyl-furan-2-carboxylic acid in the solvent, so that 5-formyl-furan-2-carboxylic acid is uniformly dissolved in the mixed solvent, so that it is fully contacted with the catalyst and hydrogen, thereby being reduced to 5-hydroxymethyl-furan-2-carboxylic acid with better water solubility, further improving the purification effect. In the present invention, the selection range of the amount of organic solvent and water used in step (1) is relatively wide, as long as the 2,5-furandicarboxylic acid raw material containing 5-formyl-furan-2-carboxylic acid impurities can be fully dissolved. Preferably, in step (1), the volume ratio of the organic solvent to water is 0.5-5:1, preferably 1-3.5:1, for example, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1 and values between any two groups. The advantage of adopting this preferred embodiment is that within this range, the solvent has a higher solubility for 2,5-furandicarboxylic acid and 5-formyl-furan-2-carboxylic acid, thereby improving the purification effect.
[0039] In the present invention, preferably, in step (1), the amount of the organic solvent and water used is such that the concentration of the 2,5-furandicarboxylic acid raw material containing 5-formyl-furan-2-carboxylic acid impurity is 20-150 g / L, preferably 25-50 g / L.
[0040] In the present invention, preferably, in step (1), the mass ratio of the selective hydrogenation catalyst to the 5-formyl-furan-2-carboxylic acid impurity is 1:0.1-20, preferably 1:0.2-10, more preferably 1:0.5-5, for example, it can be 1:0.5, 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, 1:5 and values between any two groups. The advantage of adopting this preferred embodiment is that the selective hydrogenation reaction of 5-formyl-furan-2-carboxylic acid is achieved by using a suitable catalyst dosage under the condition of avoiding the occurrence of side reactions.
[0041] In the present invention, preferably, in step (1), the temperature of the hydrogenation reaction is 80-160°C, more preferably 80-120°C, for example, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C and values between any two groups. Within the above preferred temperature range, it is beneficial for the reactants to be fully dissolved in the aforementioned preferred organic solvent of the present invention, which is beneficial for the full progress of the hydrogenation reaction, and effectively improves the recovery rate of 2,5-furandicarboxylic acid in the present invention. At the same time, it is avoided that the reaction temperature is too high to cause side reactions such as hydrogenation of carbon-carbon double bonds and carboxyl hydrogenation in 2,5-furandicarboxylic acid, and it is avoided that the temperature is too low to dissolve the reactants and it is not easy to react.
[0042] In the present invention, preferably, in step (1), the time of the hydrogenation reaction is 1-20 h, more preferably 1-15 h, and even more preferably 1-10 h, for example, it can be 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, 10 h and values between any two groups.
[0043] In the present invention, preferably, in step (1), the pressure of the hydrogen is 0.5-4 MPa, more preferably 1-3 MPa. By selecting the hydrogenation conditions within the above preferred range, the side reactions are suppressed and the recovery rate and purity of 2,5-furandicarboxylic acid are improved.
[0044] In the present invention, preferably, the content of Pd is 0.1-1% by mass, more preferably 0.1-0.5% by mass, based on the total amount of the selective hydrogenation catalyst.
[0045] In the present invention, preferably, the pore size of the nitrogen-doped nanocarbon cage is 2-20 nm.
[0046] In the present invention, preferably, based on the total molar amount of nitrogen, the molar content of pyrrolic nitrogen and / or pyridinic nitrogen in the nitrogen on the surface of the nitrogen-doped nanocarbon cage measured by X-ray photoelectron spectroscopy is greater than 90%.
[0047] In the present invention, preferably, the molar ratio of pyrrolic nitrogen to pyridinic nitrogen in the nitrogen on the surface of the nitrogen-doped nanocarbon cage measured by X-ray photoelectron spectroscopy is greater than 5. The nitrogen species on the surface of the nitrogen-doped nanocarbon cage provided by the present invention are two species of pyridinic nitrogen and pyrrolic nitrogen, which is beneficial to improving the activity of the selective hydrogenation catalyst in the selective hydrogenation reaction of 5-formyl-furan-2-carboxylic acid impurities to 5-hydroxymethyl-furan-2-carboxylic acid.
[0048] In the present invention, preferably, based on the total molar amount of nitrogen, the molar content of pyrrolic nitrogen in the nitrogen on the surface of the nitrogen-doped nanocarbon cage measured by X-ray photoelectron spectroscopy is 85.8-100%, and the molar content of pyridinic nitrogen is 0-14.2%.
[0049] In the present invention, preferably, the nitrogen-doped nanocarbon cage may also contain oxygen, which may be oxygen in various forms formed in the nitrogen-doped nanocarbon cage during the preparation of the nitrogen-doped nanocarbon cage. Preferably, the molar content of carbon on the surface of the nitrogen-doped nanocarbon cage measured by X-ray photoelectron spectroscopy is 89-92%, the molar content of nitrogen is 1-3%, and the molar content of oxygen is 5-10%.
[0050] In the present invention, preferably, the nitrogen-doped nanocarbon cage may contain doping elements known to those skilled in the art that can be applied to carbon materials. Preferably, the nitrogen-doped nanocarbon cage does not contain elements such as nickel, sulfur, boron, phosphorus, fluorine, chlorine, bromine, and iodine.
[0051] In the present invention, preferably, the BET specific surface area of the nitrogen-doped nanocarbon cage is 400-800 m 2 The advantages of adopting this preferred embodiment are that the metal components can be better dispersed, and mass transfer in the reaction process can be promoted, thereby effectively improving the catalyst activity and target product selectivity.
[0052] In the present invention, preferably, the total pore volume of the nitrogen-doped nanocarbon cage is 0.9-1.5 cm 3 / g.
[0053] In the present invention, preferably, the nitrogen-doped nanocarbon cage has a double mesopore distribution peak, and the double mesopore distribution peaks correspond to the first most probable pore size and the second most probable pore size, respectively, the first most probable pore size is 3.5-4nm, and the second most probable pore size is 6-9.5nm. In this preferred embodiment, the small pore size further provides a large specific surface area for the material, increases the active sites, and the large pore size provides a diffusion channel for molecules or ions, accelerates the mass transfer rate and provides higher stability.
[0054] In the present invention, preferably, in the Raman curve of the nitrogen-doped nanocarbon cage, I D / I G The range is 0.2-1, and more preferably 0.3-0.8. The nitrogen-doped nanocarbon cage of the present invention has obvious D peak and G peak, and has a certain degree of graphitization.
[0055] In a preferred embodiment, the nitrogen-doped nanocarbon cage is prepared by the following method:
[0056] (1) providing a solution containing a transition metal salt, a nitrogen-containing organic carboxylic acid and a solvent, and then drying to obtain a precursor, wherein the nitrogen-containing organic carboxylic acid is ethylenediaminetetraacetic acid; and the molar ratio of the transition metal salt to the nitrogen-containing organic carboxylic acid is 1:0.6-1 in terms of transition metal element;
[0057] (2) pyrolyzing the precursor obtained in step (1) at high temperature under an inert atmosphere or a reducing atmosphere to obtain a pyrolysis product;
[0058] (3) The pyrolysis product is acid-washed, and then solid-liquid separated, washed and dried.
[0059] In a preferred embodiment, the preparation method of the nitrogen-doped nanocarbon cage is achieved by using a specific nitrogen-containing organic carboxylic acid and controlling a specific ratio of a transition metal salt to the specific nitrogen-containing organic carboxylic acid, wherein the nitrogen-doped nanocarbon cage has a hollow cage-like structure with a diameter of 2-200 nm; based on the total molar amount of nitrogen, the molar content of pyrrole nitrogen and / or pyridine nitrogen in the nitrogen on the surface of the nitrogen-doped nanocarbon cage measured by X-ray photoelectron spectroscopy is greater than 85%. The preparation method has simple equipment and is easy to operate. In some embodiments, the nitrogen-doped nanocarbon cage can be obtained by simple mixing, pyrolysis and acid washing in a pure water phase and under normal pressure conditions.
[0060] In the present invention, in the process of preparing nitrogen-doped nanocarbon cages, there is no particular limitation on the amount of each substance used in step (1). Preferably, in step (1), the molar ratio of the transition metal salt to the nitrogen-containing organic carboxylic acid in terms of transition metal element is 1:0.6-1, preferably 1:0.6-0.9. The molar ratio of the transition metal salt to the nitrogen-containing organic carboxylic acid in terms of transition metal element is within the above-defined range, which is conducive to controlling the nitrogen content and the type of nitrogen species, so that the nitrogen on the surface of the obtained nitrogen-doped nanocarbon cage exists in the form of pyrrolic nitrogen and / or pyridinic nitrogen.
[0061] In the present invention, preferably, the transition metal salt and the nitrogen-containing organic carboxylic acid are used in such an amount that the molar content of carbon on the surface of the prepared nitrogen-doped nanocarbon cage is 89-92%, the molar content of nitrogen is 1-3%, and the molar content of oxygen is 5-10%.
[0062] In the present invention, preferably, the amount of the transition metal salt and the nitrogen-containing organic carboxylic acid is such that the nitrogen on the surface of the obtained nitrogen-doped nanocarbon cage is mainly in the form of pyrrolic nitrogen and / or pyridinic nitrogen, and the molar content of pyrrolic nitrogen and / or pyridinic nitrogen in the nitrogen on the surface of the nitrogen-doped nanocarbon cage measured by X-ray photoelectron spectroscopy is greater than 85%, preferably greater than 90%, based on the total molar amount of nitrogen.
[0063] In the present invention, the nitrogen-doped nanocarbon cage preparation process does not particularly limit the type of transition metal salt in step (1), and the conventionally defined transition metal salts in the art are applicable to the present invention. Preferably, in step (1), the transition metal salt is selected from at least one of an organic acid salt of a transition metal, a carbonate of a transition metal, and a basic carbonate of a transition metal, and more preferably a carbonate of a transition metal and / or a basic carbonate of a transition metal.
[0064] In the present invention, the nitrogen-doped nanocarbon cage preparation process has a wide range of transition metal types to be selected in step (1). Preferably, the transition metal is a metal element of Group VIII, more preferably at least one of iron, cobalt, nickel and copper, and more preferably nickel.
[0065] In the present invention, preferably, the transition metal salt is selected from basic nickel carbonate and / or nickel acetate.
[0066] In the present invention, in the preparation process of nitrogen-doped nanocarbon cages, in step (1), there is no particular limitation on the method for forming the solution, for example, the solution may be formed by heating, and more preferably by heating and stirring. The present invention also has no particular limitation on the heating temperature and stirring rate, as long as the solution can be formed.
[0067] In the present invention, preferably, in step (1), the precursor is a precursor obtained by dissolving a transition metal salt and a nitrogen-containing organic carboxylic acid in a solvent to form a homogeneous solution, and then removing the solvent in the homogeneous solution. The present invention has no particular limitation on the type of the solvent, and is subject to the ability to form a homogeneous solution. Preferably, the solvent is water and / or ethanol, more preferably water; the present invention has no particular limitation on the amount of the solvent, and is also subject to the ability to form a homogeneous solution. The solvent in the homogeneous solution can be removed by direct evaporation, and the evaporation temperature and process can adopt the existing technology known to those skilled in the art. For example, the solvent in the homogeneous solution can be removed by heating and evaporating to dryness.
[0068] In the present invention, the preparation process of nitrogen-doped nanocarbon cages has a wide range of selection conditions for high-temperature pyrolysis in step (2). Preferably, the high-temperature pyrolysis conditions are: a heating rate of 0.5-30°C / min, a high-temperature pyrolysis temperature of 850-1000°C, and a constant temperature time of 20-600min; further preferably, the high-temperature pyrolysis conditions are: a heating rate of 1-20°C / min, a high-temperature pyrolysis temperature of 850-950°C, and a constant temperature time of 60-480min. The above-mentioned high-temperature pyrolysis conditions can adjust the type of nitrogen species and the removal rate of transition metals. For example, if the temperature is too low, it is not conducive to the removal of transition metals in the material, and if the temperature is too high, it is easy to generate nitrogen-doped nanocarbon cages containing other nitrogen species.
[0069] According to a preferred embodiment of the present invention, in the preparation process of nitrogen-doped nanocarbon cages, in step (2), the temperature is raised to the temperature of the high-temperature pyrolysis by a two-stage heating method, specifically: first, the temperature is raised to 400-800°C, preferably 500-700°C, at a rate of 1-20°C / min, preferably at a rate of 5-10°C / min, and the temperature is kept constant for 20-600min, preferably 60-480min, and then the temperature is continued to be raised to the temperature of the high-temperature pyrolysis at a rate of 1-20°C / min, preferably at a rate of 5-10°C / min, and the temperature is kept constant for 20-600min, preferably 60-480min. In the present invention, the heating method of two stages is conducive to the formation of nitrogen-doped nanocarbon cages containing only pyrrole nitrogen in the nitrogen species or only pyrrole nitrogen and pyridine nitrogen in the nitrogen species.
[0070] In the present invention, the type of inert atmosphere in step (2) is not particularly limited in the preparation process of nitrogen-doped nanocarbon cages, and any inert atmosphere conventionally defined in the art is applicable to the present invention. Preferably, in step (2), the inert atmosphere is selected from at least one of nitrogen, argon, neon and helium.
[0071] In the present invention, the type of reducing atmosphere in step (2) of the preparation process of nitrogen-doped nanocarbon cages is not particularly limited, and any reducing atmosphere conventionally defined in the art is applicable to the present invention. Preferably, the reducing atmosphere is provided by hydrogen and optionally an inert gas, and the inert gas is selected from at least one of nitrogen, argon, neon and helium.
[0072] In the present invention, in the preparation process of nitrogen-doped nanocarbon cages, in step (3), the pyrolysis product is pickled with a pickling agent, which can be specifically: mixing the pyrolysis product with the pickling agent. The present invention has no particular limitation on the mixing method, and the mixture can be mixed by ultrasound or stirring. The pickling agent can be an acid conventionally used in the art, as long as it can remove the transition metal in the pyrolysis product. Preferably, the pickling agent is an inorganic acid aqueous solution and / or an organic acid aqueous solution, more preferably at least one of a hydrochloric acid aqueous solution, a sulfuric acid aqueous solution, a nitric acid aqueous solution and a citric acid aqueous solution, and more preferably a hydrochloric acid aqueous solution.
[0073] In the present invention, in the preparation process of nitrogen-doped nanocarbon cages, in step (3), the concentration of the pickling agent is not particularly limited. Preferably, the concentration of the inorganic acid aqueous solution and / or the organic acid aqueous solution is 0.1-10 mol / L.
[0074] In the present invention, in the preparation process of nitrogen-doped nanocarbon cages, in step (3), the pH of the pickling agent is not particularly limited. Preferably, the pH value of the inorganic acid aqueous solution and / or the organic acid aqueous solution is less than 7. The present invention has no particular requirements for the amount of the pickling agent, as long as it can remove the transition metal in the pyrolysis product.
[0075] In the present invention, preferably, in the preparation process of nitrogen-doped nanocarbon cages, in step (3), the acid pickling temperature is 20-120° C. and the time is 0.1-48 h; more preferably, the temperature is 60-100° C. and the time is 4-12 h.
[0076] In the present invention, in the preparation process of nitrogen-doped nanocarbon cages, in step (3), there is no particular limitation on the solid-liquid separation method, and it can be carried out by a solid-liquid separation method known in the art, such as filtering.
[0077] In the present invention, preferably, in the preparation process of nitrogen-doped nanocarbon cages, in step (3), the washing is used to remove the acid and metal ions remaining on the nitrogen-doped nanocarbon cages during the acid washing process. Therefore, various water washing methods that can wash the nitrogen-doped nanocarbon cages to neutrality are applicable to the present invention.
[0078] In the present invention, preferably, in the preparation process of nitrogen-doped nanocarbon cages, in step (3), the drying is used to remove water from the nitrogen-doped nanocarbon cages. For example, normal pressure drying or reduced pressure drying can be used. Preferably, the drying conditions may include: a temperature of 80-140° C. and a time of 6-10 h.
[0079] In the art, the conventionally defined preparation methods of the selective hydrogenation catalyst are applicable to the present invention, and can be prepared by impregnation, such as isochoric impregnation, incipient wetness impregnation, ion exchange, deposition-precipitation or vacuum impregnation. According to a specific embodiment of the present invention, the selective hydrogenation catalyst can be prepared by the incipient wetness impregnation method: a solution containing a Pd precursor is introduced into a nitrogen-doped nanocarbon cage carrier and then impregnated at room temperature for 1-12 hours, and then dried in an oven at 100-140°C for 6-24 hours, and the obtained catalyst precursor is reduced at a temperature of 200-600°C for 1-5 hours in a reducing atmosphere (e.g., a mixed atmosphere of hydrogen and nitrogen) to obtain a selective hydrogenation catalyst. In the present invention, the type of Pd precursor is not particularly limited, and the Pd is provided by a solution containing a Pd precursor, and the Pd-containing precursor is selected from a soluble salt containing Pd, preferably a chloride and / or a nitrate, such as palladium chloride and / or palladium nitrate. In the present invention, the drying conditions are not particularly limited. Preferably, the drying conditions include: a temperature of 80-120°C and a time of 8-20h. In the present invention, there is no particular limitation on the type of reducing atmosphere, and the reducing atmospheres conventionally defined in the art are applicable to the present invention. Preferably, the reducing atmosphere is hydrogen and optionally an inert gas, and the inert gas is selected from at least one of nitrogen, argon, neon and helium, and is further preferably hydrogen and nitrogen. According to a preferred embodiment of the present invention, the content of hydrogen in the reducing atmosphere is 5-30% by volume, and the content of nitrogen is 70-95% by volume. In the present invention, the range of reduction conditions is relatively wide. Preferably, in step S2, the reducing conditions include: a temperature of 200-600°C, a time of 1-5h, and a reducing atmosphere volume space velocity of 1-100h -1 Further preferably, the reduction conditions include: temperature of 300-500°C, time of 2-4h, and volumetric air velocity of the reducing atmosphere of 5-50h -1 .
[0080] In the present invention, the product obtained in step (1) is a mixture containing a selective hydrogenation catalyst, and the selective hydrogenation catalyst is separated by solid-liquid separation in step (2). The solid-liquid separation can be carried out in a conventional operation mode in the art, and the present invention does not specifically limit this. For example, the product can be filtered. Preferably, in step (2), the temperature of the solid-liquid separation is 20-100°C, preferably 50-100°C. Using the solid-liquid separation temperature within the above preferred range helps to ensure that 2,5-furandicarboxylic acid and 5-hydroxymethyl-furan-2-carboxylic acid are in a completely dissolved state during the separation process, thereby being fully separated from the selective hydrogenation catalyst.
[0081] In the present invention, preferably, the method further comprises: removing the solvent from the product obtained by the solid-liquid separation to obtain a 2,5-furandicarboxylic acid solid containing 5-hydroxymethyl-furan-2-carboxylic acid impurity. The present invention has no particular limitation on the method for removing the solvent, for example, an evaporation method can be used.
[0082] In the present invention, since the solubility of 5-hydroxymethyl-furan-2-carboxylic acid in water is significantly higher than that of 2,5-furandicarboxylic acid and 5-formyl-furan-2-carboxylic acid, 5-formyl-furan-2-carboxylic acid is hydrogenated to 5-hydroxymethyl-furan-2-carboxylic acid with high selectivity, and then the 5-hydroxymethyl-furan-2-carboxylic acid impurity is dissolved in water by washing, and the remaining solid is the purified 2,5-furandicarboxylic acid product.
[0083] In the present invention, there is no particular limitation on the specific operation mode and number of washing in step (2). Preferably, the number of washing is 1-10 times, more preferably 2-6 times.
[0084] In the present invention, preferably, the recovery rate of the 2,5-furandicarboxylic acid product obtained by the purification method is greater than 90%, and the content of 2,5-furandicarboxylic acid in the 2,5-furandicarboxylic acid product is greater than 99%.
[0085] Wherein, the recovery rate (%) = the mass of the 2,5-furandicarboxylic acid product / the mass of the 2,5-furandicarboxylic acid in the raw material × 100%.
[0086] The present invention will be described in detail below through examples.
[0087] Unless otherwise specified, all reagents used in the present invention are analytically pure and commercially available.
[0088] The surface morphology of the material was characterized by high-resolution transmission electron microscopy (HRTEM), the model of the high-resolution transmission electron microscope used was JEM-2100 (JEOL Ltd.), and the test conditions of the high-resolution transmission electron microscope were: the acceleration voltage was 200 kV. The diameter of the nitrogen-doped nanocarbon cage was measured by electron microscope images.
[0089] The pore structure properties of the material were detected by the BET test method. Specifically, the Quantachrome AS-6B analyzer was used for the determination. The specific surface area and pore volume of the material were obtained by the Brunauer-Emmett-Taller (BET) method, and the mesopore distribution curve was calculated by the desorption curve according to the Barrett-Joyner-Halenda (BJH) method.
[0090] The content of each element on the surface of the material was determined by X-ray photoelectron spectroscopy (XPS). The X-ray photoelectron spectroscopy analysis was carried out on an ESCALab250 X-ray photoelectron spectrometer equipped with Thermo Avantage V5.926 software from Thermo Scientific. The excitation source was monochromatic Al Kα X-ray with an energy of 1486.6 eV and a power of 150 W. The penetration energy used for narrow scanning was 30 eV. The basic vacuum during the analysis test was 6.53×10 -9 The electron binding energy was calibrated with the C1s peak (284.6 eV) of elemental carbon. The data were processed on Thermo Avantage software, and the sensitivity factor method was used for quantitative analysis in the analysis module.
[0091] The graphitization degree of the material was characterized by Raman spectroscopy, 1355 cm -1 The peak (D peak) is attributed to structural defects and is amorphous carbon, 1585cm -1 The peak (G peak) is attributed to the carbon in the planar structure. Usually I D / I G (D peak and G peak intensity ratio) to characterize the degree of graphitization of the material. D / I G The higher the value, the more defects there are and the lower the degree of graphitization. The Raman spectrum of the material is obtained using a RM2000 micro-confocal Raman spectrometer (product of Reinshaw Company), and the technical indicators are: the excitation source is a He-Ne laser with a wavelength of 525nm.
[0092] In the present invention, the purified product of 2,5-furandicarboxylic acid is analyzed by high performance liquid chromatography, and the conditions of high performance liquid chromatography include using an Alltech OA-1000 organic acid chromatographic column, a UV detector, a mobile phase of 0.005 mol / L H2SO4 aqueous solution, a flow rate of 0.6 mL / min, and a column temperature of 70°C.
[0093] Preparation Examples 1-3 are used to illustrate the preparation of nitrogen-doped nanocarbon cages.
[0094] Preparation Example 1
[0095] (1) Weigh 15 g of basic nickel carbonate and 20.9 g of ethylenediaminetetraacetic acid (molar ratio of 1:0.7), add them into a beaker containing 40 mL of deionized water, stir and mix them evenly at 80° C., and continue to heat and evaporate to obtain a solid precursor.
[0096] (2) The precursor obtained in step (1) is placed in a porcelain boat, and then the porcelain boat is placed in the constant temperature zone of a tube furnace, nitrogen is introduced at a flow rate of 80 mL / min, and the temperature is increased to 600°C at a rate of 10°C / min. After the temperature is maintained for 1 hour, the temperature is further increased to 900°C at a rate of 10°C / min, and the temperature is maintained for 2 hours. The heating is stopped, and the mixture is cooled to room temperature in a nitrogen atmosphere to obtain a pyrolysis product.
[0097] (3) The pyrolysis product obtained in step (2) is added to an aqueous solution containing 2M hydrochloric acid and stirred at 90°C for 8 hours, then filtered, the filtrate is collected, and then washed with deionized water until the filtrate is neutral, and then the filter cake is dried in a constant temperature oven at 120°C for 6 hours to obtain nitrogen-doped nanocarbon cage Z1.
[0098] Figure 1 TEM image of the nitrogen-doped nanocarbon cage. It can be seen from the image that the nitrogen-doped nanocarbon cage is a hollow cage-shaped nanocarbon material with a diameter of 5-20 nm.
[0099] Figure 2 This is the XPS spectrum of the nitrogen-doped nanocarbon cage. It can be seen from the figure that in addition to carbon, there are also oxygen and nitrogen elements on the surface of the nitrogen-doped nanocarbon cage. The atomic molar percentage of each element can be calculated from the peak area, among which carbon is 90.06%, oxygen is 8.4%, and nitrogen is 1.54%.
[0100] Figure 3 This is the N1s peak spectrum of the XPS of the nitrogen-doped nanocarbon cage. From the figure, it can be seen that the nitrogen on the surface of the nitrogen-doped nanocarbon cage exists in the form of pyrrole nitrogen, and there is no other form of nitrogen species. Based on the total molar amount of nitrogen, the content of pyrrole nitrogen is 100%.
[0101] BET test shows that the BET specific surface area of the nitrogen-doped nanocarbon cage is 466.24 m 2 / g, pore volume 0.978cm 3 / g. Figure 4 : is the BJH pore size distribution curve of the nitrogen-doped nanocarbon cage. It can be seen from the figure that the pore size distribution curve of the nitrogen-doped nanocarbon cage has two mesopore distribution peaks at 3.68nm and 6.15nm.
[0102] Raman analysis showed that the nitrogen-doped nanocarbon cage had obvious D peak and G peak. D / I G It is 0.5266, indicating that the nitrogen-doped nanocarbon cage has a certain degree of graphitization.
[0103] Preparation Example 2
[0104] (1) Weigh 15 g of basic nickel carbonate and 20.9 g of ethylenediaminetetraacetic acid (molar ratio of 1:0.7), add them into a beaker containing 40 mL of deionized water, stir and mix them evenly at 80° C., and continue to heat and evaporate to obtain a solid precursor.
[0105] (2) The precursor obtained in step (1) is placed in a porcelain boat, and then the porcelain boat is placed in the constant temperature zone of a tube furnace, nitrogen is introduced at a flow rate of 80 mL / min, and the temperature is increased to 600°C at a rate of 10°C / min. After the temperature is maintained for 1 hour, the temperature is further increased to 850°C at a rate of 10°C / min, and the temperature is maintained for 2 hours. The heating is stopped, and the mixture is cooled to room temperature in a nitrogen atmosphere to obtain a pyrolysis product.
[0106] (3) The pyrolysis product obtained in step (2) is added to an aqueous solution containing 2M hydrochloric acid and stirred at 100°C for 8 hours, then filtered, the filtrate is collected, and then washed with deionized water until the filtrate is neutral, and then the filter cake is dried in a constant temperature oven at 120°C for 6 hours to obtain nitrogen-doped nanocarbon cage Z2.
[0107] High-resolution transmission electron microscopy observation and measurement show that the nitrogen-doped nanocarbon cage has a hollow cage-like structure with a diameter of 5-20 nm.
[0108] XPS measured that in addition to carbon, oxygen and nitrogen elements existed on the surface of the nitrogen-doped nanocarbon cage. The atomic percentage of each element can be calculated from the peak area, among which carbon is 91.05%, oxygen is 7.48%, and nitrogen is 1.47%. The nitrogen element of the nitrogen-doped nanocarbon cage was separated into peaks, such as Figure 5 As shown in the figure, it can be seen that the nitrogen on the surface of the nitrogen-doped nanocarbon cage exists in two forms: pyrrolic nitrogen and pyridinic nitrogen. Based on the total molar amount of nitrogen, the content of pyrrolic nitrogen is 92.01% and the content of pyridinic nitrogen is 7.99%.
[0109] BET test shows that the BET specific surface area of the nitrogen-doped nanocarbon cage is 713.17 m 2 / g, pore volume 1.482cm 3 In the BJH pore size distribution curve of the nitrogen-doped nanocarbon cage, there are two mesopore distribution peaks at 3.71 nm and 6.25 nm.
[0110] Raman analysis showed that the nitrogen-doped nanocarbon cage had obvious D peak and G peak. D / I G It is 0.703, indicating that the nitrogen-doped nanocarbon cage has a certain degree of graphitization.
[0111] Preparation Example 3
[0112] (1) Weigh 15 g of nickel acetate and 22.3 g of ethylenediaminetetraacetic acid (molar ratio of 1:0.9), add them into a beaker containing 40 mL of deionized water, stir and mix at 80° C., and continue heating and evaporating to obtain a solid precursor.
[0113] (2) The precursor obtained in step (1) is placed in a porcelain boat, and then the porcelain boat is placed in the constant temperature zone of a tubular furnace, nitrogen is introduced at a flow rate of 150 mL / min, and the temperature is increased to 950°C at a rate of 20°C / min. After maintaining the constant temperature for 2 hours, heating is stopped, and the mixture is cooled to room temperature under a nitrogen atmosphere to obtain a pyrolysis product.
[0114] (3) The pyrolysis product obtained in step (2) is added to an aqueous solution containing 2M nitric acid and stirred at 100°C for 8 hours, then filtered, the filtrate is collected, and then washed with deionized water until the filtrate is neutral, and then the filter cake is dried in a constant temperature oven at 120°C for 6 hours to obtain nitrogen-doped nanocarbon cage Z3.
[0115] High-resolution transmission electron microscopy observation and measurement show that the nitrogen-doped nanocarbon cage has a hollow cage-like structure with a diameter of 5-20 nm.
[0116] XPS measured that the surface of the nitrogen-doped nanocarbon cage contained not only carbon, but also oxygen and nitrogen. The atomic percentage of each element can be calculated from the peak area, where carbon was 89.96%, oxygen was 7.97%, and nitrogen was 2.07%. The nitrogen element of the nitrogen-doped nanocarbon cage was separated into peaks, such as Figure 6 As shown in the figure, it can be seen that the nitrogen on the surface of the nitrogen-doped nanocarbon cage exists in two forms: pyrrolic nitrogen and pyridinic nitrogen. Based on the total molar amount of nitrogen, the content of pyrrolic nitrogen is 85.80% and the content of pyridinic nitrogen is 14.20%.
[0117] BET test shows that the BET specific surface area of the nitrogen-doped nanocarbon cage is 512.17 m 2 / g, pore volume 1.123cm 3 In the BJH pore size distribution curve of the nitrogen-doped nanocarbon cage, there are two mesopore distribution peaks at 3.59 nm and 9.25 nm.
[0118] Raman analysis showed that the nitrogen-doped nanocarbon cage had obvious D peak and G peak. D / I G It is 0.324, indicating that the nitrogen-doped nanocarbon cage has a certain degree of graphitization.
[0119] Preparation Examples 4-8 are used to illustrate the preparation of selective hydrogenation catalysts.
[0120] Preparation Example 4
[0121] Nitrogen-doped nanocarbon cage-supported Pd-based catalysts were prepared by incipient wetness impregnation method.
[0122] Mix 0.5 mL of 0.1 mol / L PdCl2 solution and 3.0 mL of deionized water, stir evenly, then add 1.00 g of the nitrogen-doped nanocarbon cage (Z1) obtained in Preparation Example 1 to the mixture, stir and immerse for 10 hours at room temperature, evaporate the water, and then dry in an oven at 110°C for 12 hours to obtain a catalyst precursor. The Pd loading is about 0.5% (mass percentage). The precursor prepared in the above steps is placed in a quartz tube and reduced at 500°C for 3 hours in 20% H2+N2 at a volume space velocity of 20 h -1 , a selective hydrogenation catalyst A1 having a Pd loading of 0.5 mass % was obtained (wherein the loading amount is based on the total amount of the catalyst).
[0123] Preparation Example 5
[0124] According to the method of Preparation Example 4, except that the nitrogen-doped nanocarbon cage (Z2) obtained in Preparation Example 2 was used as a carrier to prepare a selective hydrogenation catalyst A2 with a Pd loading of 0.5 mass% (wherein the loading is based on the total amount of the catalyst).
[0125] Preparation Example 6
[0126] According to the method of Preparation Example 4, except that the nitrogen-doped nanocarbon cage (Z3) obtained in Preparation Example 3 was used as a carrier to prepare a selective hydrogenation catalyst A3 with a Pd loading of 0.5 mass% (wherein the loading is based on the total amount of the catalyst).
[0127] Preparation Example 7
[0128] The method of Preparation Example 4 was followed, except that the amount of 0.1 mol / L PdCl2 solution added was 0.2 mL, and a selective hydrogenation catalyst A4 with a Pd loading of 0.2 mass % was prepared (wherein the loading was based on the total amount of the catalyst).
[0129] Preparation Example 8
[0130] The method of Preparation Example 4 was followed, except that 1 mL of 0.1 mol / L PdCl2 solution was added to prepare a selective hydrogenation catalyst A5 having a Pd loading of 1 mass % (wherein the loading is based on the total amount of the catalyst).
[0131] Examples 1-8 and Comparative Example 1 are used to illustrate the purification of 2,5-furandicarboxylic acid containing 5-formyl-furan-2-carboxylic acid as an impurity.
[0132] In order to better quantitatively investigate the reaction of 5-formyl-furan-2-carboxylic acid and 2,5-furandicarboxylic acid in the present method, commercially available 2,5-furandicarboxylic acid and 5-formyl-furan-2-carboxylic acid reagents are mechanically mixed to prepare a 2,5-furandicarboxylic acid raw material containing 5-formyl-furan-2-carboxylic acid impurities. Specifically:
[0133] Taking 2,5-furandicarboxylic acid having a 5-formyl-furan-2-carboxylic acid impurity content of 10% by mass as an example, 900 mg of 2,5-furandicarboxylic acid solid powder and 100 mg of 5-formyl-furan-2-carboxylic acid solid powder were weighed separately, and then ground and mixed in a mortar to obtain a 2,5-furandicarboxylic acid raw material having a 5-formyl-furan-2-carboxylic acid impurity content of 10% by mass.
[0134] According to this method, 2,5-furandicarboxylic acid raw materials with 5-formyl-furan-2-carboxylic acid impurity contents of 1% by mass and 5% by mass were prepared respectively.
[0135] Example 1
[0136] This Example 1 is used to illustrate the use of the selective hydrogenation catalyst A1 obtained in Preparation Example 4 as the catalyst in step (1) to purify 2,5-furandicarboxylic acid containing 5-formyl-furan-2-carboxylic acid as an impurity.
[0137] (1) 50 mg of selective hydrogenation catalyst A1, 1000 mg of 2,5-furandicarboxylic acid with a 5-formyl-furan-2-carboxylic acid impurity content of 10% (i.e., containing 900 mg of 2,5-furandicarboxylic acid and 100 mg of 5-formyl-furan-2-carboxylic acid), 15 mL of 1,4-dioxane, and 15 mL of water were added to a reactor. H2 was introduced into the reactor for replacement three times, and the temperature was raised under low pressure with stirring to a predetermined reaction temperature of 80° C. H2 was introduced again to make the pressure in the reactor 1 MPa. After the reaction was continued for 8 hours, heating was stopped, and the pressure was released at 80° C. and the reactor was opened.
[0138] (2) filtering the reaction solution obtained in step (1) at 80° C. to separate the catalyst, and then removing the solvent from the reaction solution by a rotary evaporator to obtain a 2,5-furandicarboxylic acid solid containing 5-hydroxymethyl-furan-2-carboxylic acid as an impurity;
[0139] (3) Wash the solid obtained in step (2) in a beaker with deionized water for 5 times. After each washing, separate the aqueous phase and the solid by centrifugation. After the remaining solid is dried and weighed, a small amount of Na2CO3 aqueous solution is added to dissolve it and the volume is fixed to 250 mL. Quantitative analysis is performed using high performance liquid chromatography.
[0140] It was determined that the remaining solid mass was 857 mg, of which the 2,5-furandicarboxylic acid content was 99.97 wt %, and the 5-formyl-furan-2-carboxylic acid content was 0.03 wt %. That is, after being treated by the method, the recovery rate of 2,5-furandicarboxylic acid was (857 mg / 900 mg×100%) 95.2%, and the purity was 99.97%.
[0141] Example 2
[0142] This example is used to illustrate the use of the selective hydrogenation catalyst A2 obtained in Preparation Example 5 as the catalyst for step (1) to purify 2,5-furandicarboxylic acid containing 5-formyl-furan-2-carboxylic acid as an impurity.
[0143] (1) 50 mg of selective hydrogenation catalyst A2, 500 mg of 2,5-furandicarboxylic acid with a 5% 5-formyl-furan-2-carboxylic acid impurity content (i.e., containing 475 mg 2,5-furandicarboxylic acid and 25 mg 5-formyl-furan-2-carboxylic acid), 10 mL of dioxane, and 10 mL of water were added to a reactor. H2 was introduced into the reactor for replacement three times, and the temperature was raised under low pressure with stirring until the temperature reached a predetermined reaction temperature of 95° C. H2 was introduced again to make the pressure in the reactor 2 MPa. After the reaction was continued for 2 hours, heating was stopped, and the pressure was released and the reactor was opened when the temperature dropped to 80° C.
[0144] (2) filtering the reaction solution obtained in step (1) at 80° C. to separate the catalyst, and then removing the solvent from the reaction solution by a rotary evaporator to obtain a 2,5-furandicarboxylic acid solid containing 5-hydroxymethyl-furan-2-carboxylic acid as an impurity;
[0145] (3) Wash the solid obtained in step (2) in a beaker with deionized water for 5 times. After each washing, separate the aqueous phase and the solid by centrifugation. After the remaining solid is dried and weighed, a small amount of Na2CO3 aqueous solution is added to dissolve it and the volume is fixed to 250 mL. Quantitative analysis is performed using high performance liquid chromatography.
[0146] It was determined that the remaining solid mass was 451 mg, of which the 2,5-furandicarboxylic acid content was 99.45 wt %, and the 5-formyl-furan-2-carboxylic acid content was 0.55 wt %. That is, after being treated by the method, the recovery rate of 2,5-furandicarboxylic acid was (451 mg / 475 mg×100%) 94.9%, and the purity was 99.45%.
[0147] Example 3
[0148] This example is used to illustrate the use of the selective hydrogenation catalyst A3 obtained in Preparation Example 6 as the catalyst in step (1) to purify 2,5-furandicarboxylic acid containing 5-formyl-furan-2-carboxylic acid as an impurity.
[0149] (1) 10 mg of selective hydrogenation catalyst A3, 2000 mg of 2,5-furandicarboxylic acid with a 5-formyl-furan-2-carboxylic acid impurity content of 1% (i.e., containing 1980 mg of 2,5-furandicarboxylic acid and 20 mg of 5-formyl-furan-2-carboxylic acid), 15 mL of dioxane, and 15 mL of water were added to a reactor. H2 was introduced into the reactor for displacement three times, and the temperature was raised under low pressure with stirring to a predetermined reaction temperature of 120° C. H2 was introduced again to make the pressure in the reactor 1.5 MPa. After the reaction was continued for 2 hours, heating was stopped, and the pressure was released and the reactor was opened when the temperature dropped to 80° C.
[0150] (2) filtering the reaction solution obtained in step (1) at 80° C. to separate the catalyst, and then removing the solvent from the reaction solution by a rotary evaporator to obtain a 2,5-furandicarboxylic acid solid containing 5-hydroxymethyl-furan-2-carboxylic acid as an impurity;
[0151] (3) Wash the solid obtained in step (2) in a beaker with deionized water for 5 times. After each washing, separate the aqueous phase and the solid by centrifugation. After the remaining solid is dried and weighed, a small amount of Na2CO3 aqueous solution is added to dissolve it and the volume is fixed to 250 mL. Quantitative analysis is performed using high performance liquid chromatography.
[0152] It was determined that the remaining solid mass was 1913 mg, of which the content of 2,5-furandicarboxylic acid was 99.91 wt %, and the content of 5-formyl-furan-2-carboxylic acid was 0.09 wt %. That is, after being treated by the present method, the recovery rate of 2,5-furandicarboxylic acid was (1913 mg / 1980 mg×100%) 96.6%, and the purity was 99.91%.
[0153] Example 4
[0154] The reaction was carried out according to the method of Example 1, except that the catalyst used in step (1) was 50 mg of the selective hydrogenation catalyst A4 obtained in Preparation Example 7, and the reaction time was 12 hours.
[0155] It was determined that the remaining solid mass was 882 mg, of which the 2,5-furandicarboxylic acid content was 99.21 wt %, and the 5-formyl-furan-2-carboxylic acid content was 0.79 wt %. That is, after being treated by the method, the recovery rate of 2,5-furandicarboxylic acid was (882 mg / 900 mg×100%) 98.0%, and the purity was 99.21%.
[0156] Example 5
[0157] The reaction was carried out according to the method of Example 1, except that the catalyst used in step (1) was 50 mg of the selective hydrogenation catalyst A5 obtained in Preparation Example 8, and the reaction time was 3 hours.
[0158] It was determined that the remaining solid mass was 835 mg, of which the content of 2,5-furandicarboxylic acid was 99.96 wt %, and the content of 5-formyl-furan-2-carboxylic acid was 0.04%. That is, after being treated by the method, the recovery rate of 2,5-furandicarboxylic acid was (835 mg / 900 mg×100%) 92.8%, and the purity was 99.96%.
[0159] Example 6
[0160] The reaction was carried out according to the method of Example 1, except that the solvent used in step (1) was 20 mL of ethylene glycol dimethyl ether and 10 mL of water.
[0161] It was determined that the remaining solid mass was 815 mg, of which the 2,5-furandicarboxylic acid content was 99.15 wt %, and the 5-formyl-furan-2-carboxylic acid content was 0.85 wt %. That is, after being treated by the method, the recovery rate of 2,5-furandicarboxylic acid was (815 mg / 900 mg×100%) 90.6%, and the purity was 99.15%.
[0162] Example 7
[0163] The reaction was carried out according to the method of Example 1, except that the reaction temperature used in step (1) was 160°C.
[0164] It was determined that the remaining solid mass was 810 mg, of which the 2,5-furandicarboxylic acid content was 99.75 wt %, and the 5-formyl-furan-2-carboxylic acid content was 0.25 wt %. That is, after being treated by the method, the recovery rate of 2,5-furandicarboxylic acid was (810 mg / 900 mg×100%) 90.0%, and the purity was 99.75%.
[0165] Example 8
[0166] The reaction was carried out according to the method of Example 1, except that the reaction pressure used in step (1) was 4 MPa.
[0167] It was determined that the remaining solid mass was 821 mg, of which the content of 2,5-furandicarboxylic acid was 99.73 wt %, and the content of 5-formyl-furan-2-carboxylic acid was 0.27%. That is, after being treated by the method, the recovery rate of 2,5-furandicarboxylic acid was (821 mg / 900 mg×100%) 91.2%, and the purity was 99.73%.
[0168] Comparative Example 1
[0169] This example is used to illustrate the purification of 2,5-furandicarboxylic acid using only water as the solvent in step (1).
[0170] (1) 50 mg of selective hydrogenation catalyst A1, 1000 mg of 2,5-furandicarboxylic acid with a 5-formyl-furan-2-carboxylic acid impurity content of 10% (i.e., containing 900 mg of 2,5-furandicarboxylic acid and 100 mg of 5-formyl-furan-2-carboxylic acid), and 30 mL of water were added to a reactor. H2 was introduced into the reactor for replacement three times, and the temperature was raised under low pressure with stirring to a predetermined reaction temperature of 80° C. H2 was introduced again to make the pressure in the reactor 1 MPa. After the reaction was continued for 8 hours, heating was stopped, and the pressure was released at 80° C. and the reactor was opened.
[0171] (2) Filter the reaction solution obtained in step (1) at 80°C. Since the solubility of 2,5-furandicarboxylic acid is low under this temperature condition when water is used as the solvent, part of the 2,5-furandicarboxylic acid (including part of the unreacted 5-formyl-furan-2-carboxylic acid) does not dissolve in the reaction solution, but is filtered and separated together with the catalyst. Therefore, after one filtration, the filter cake is a mixture of black solid (catalyst) and white solid (undissolved reaction raw material). In order to analyze the content of 2,5-furandicarboxylic acid and 5-formyl-furan-2-carboxylic acid in the entire reaction system, it is necessary to repeatedly rinse the filter cake with an aqueous solution of Na2CO3 during the filtration process, so that part of the undissolved 2,5-furandicarboxylic acid and 5-formyl-furan-2-carboxylic acid reacts with Na2CO3 to form their corresponding soluble sodium salts, thereby achieving complete separation of 2,5-furandicarboxylic acid and 5-formyl-furan-2-carboxylic acid from the catalyst.
[0172] (3) All the reaction solutions and the filter cake washing solution were mixed and fixed to 500 mL, and quantitative analysis was performed using high performance liquid chromatography.
[0173] After measurement and conversion, the content of 2,5-furandicarboxylic acid in the reaction liquid and the washing liquid of the filter cake is 883 mg, and the content of 5-formyl-furan-2-carboxylic acid is 89 mg, that is, when only water is used as a solvent, under the reaction conditions of the present invention, due to the low solubility of the reaction raw materials (2,5-furandicarboxylic acid and 5-formyl-furan-2-carboxylic acid), the hydrogenation reaction effect of 5-formyl-furan-2-carboxylic acid is poor, and the effect of purifying 2,5-furandicarboxylic acid cannot be achieved.
[0174] It can be seen from the above examples that the purification method of the present invention can successfully purify 2,5-furandicarboxylic acid containing 5-formyl-furan-2-carboxylic acid as an impurity, and the recovery rate of 2,5-furandicarboxylic acid reaches more than 90% and the purity reaches more than 99.9%.
[0175] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for purifying 2,5-furandicarboxylic acid, wherein: The method comprises the following steps: (1) contacting a 2,5-furandicarboxylic acid raw material containing 5-formyl-furan-2-carboxylic acid impurity, hydrogen and a selective hydrogenation catalyst in the presence of an organic solvent and water to carry out a hydrogenation reaction; (2) subjecting the product obtained in step (1) to solid-liquid separation and washing; The selective hydrogenation catalyst comprises a carrier and an active metal component Pd loaded on the carrier, wherein the content of Pd is 0.1-2 mass %; the carrier is a nitrogen-doped nanocarbon cage; the nitrogen-doped nanocarbon cage has a hollow cage-like structure, and the BET specific surface area of the nitrogen-doped nanocarbon cage is 400-1000 m 2 / g; the pore size of the nitrogen-doped nanocarbon cage is 2-50nm; based on the total molar amount of nitrogen, the molar content of pyrrolic nitrogen and / or pyridinic nitrogen in the nitrogen on the surface of the nitrogen-doped nanocarbon cage measured by X-ray photoelectron spectroscopy is greater than 85%.
2. The method according to claim 1, wherein: In step (1), the 2,5-furandicarboxylic acid raw material containing 5-formyl-furan-2-carboxylic acid impurity is selected from the crude product obtained when 2,5-furandicarboxylic acid is produced by 5-hydroxymethylfurfural oxidation method; And / or, in step (1), based on the total amount of 2,5-furandicarboxylic acid raw material containing 5-formyl-furan-2-carboxylic acid impurity, the content of the 5-formyl-furan-2-carboxylic acid impurity is 0.1-20% by mass, preferably 0.2-15% by mass, and more preferably 0.5-10% by mass.
3. The method according to claim 1 or 2, wherein: In step (1), the organic solvent is selected from at least one of tetrahydrofuran, 1,4-dioxane and ethylene glycol dimethyl ether, preferably 1,4-dioxane; And / or, in step (1), the volume ratio of the organic solvent to water is 0.5-5:1, preferably 1-3.5:
1.
4. The method according to any one of claims 1 to 3, wherein: In step (1), the amount of the organic solvent and water used is such that the concentration of the 2,5-furandicarboxylic acid raw material containing 5-formyl-furan-2-carboxylic acid impurity is 20-150 g / L, preferably 25-100 g / L.
5. The method according to any one of claims 1 to 4, wherein: In step (1), the mass ratio of the selective hydrogenation catalyst to the 5-formyl-furan-2-carboxylic acid impurity is 1:0.1-20, preferably 1:0.2-10, and more preferably 1:0.5-5.
6. The method according to any one of claims 1 to 5, wherein: In step (1), the temperature of the hydrogenation reaction is 80-160°C, preferably 80-120°C; And / or, in step (1), the hydrogenation reaction time is 1-20h, preferably 1-15h, more preferably 1-10h; And / or, in step (1), the pressure of the hydrogen is 0.5-4 MPa, preferably 1-3 MPa.
7. The method according to any one of claims 1 to 6, wherein: Based on the total amount of the selective hydrogenation catalyst, the content of Pd is 0.1-1% by mass, preferably 0.1-0.5% by mass.
8. The method according to any one of claims 1 to 7, wherein: The pore size of the nitrogen-doped nanocarbon cage is 2-20 nm; and / or, based on the total molar amount of nitrogen, the molar content of pyrrolic nitrogen and / or pyridinic nitrogen in the nitrogen on the surface of the nitrogen-doped nanocarbon cage measured by X-ray photoelectron spectroscopy is greater than 90%; and / or, the molar ratio of pyrrolic nitrogen to pyridinic nitrogen in the nitrogen on the surface of the nitrogen-doped nanocarbon cage measured by X-ray photoelectron spectroscopy is greater than 5; And / or, based on the total molar amount of nitrogen, the molar content of pyrrolic nitrogen in the nitrogen on the surface of the nitrogen-doped nanocarbon cage measured by X-ray photoelectron spectroscopy is 85.8-100%, and the molar content of pyridinic nitrogen is 0-14.2%; And / or, the molar content of carbon on the surface of the nitrogen-doped nanocarbon cage measured by X-ray photoelectron spectroscopy is 89-92%, the molar content of nitrogen is 1-3%, and the molar content of oxygen is 5-10%; And / or, the BET specific surface area of the nitrogen-doped nanocarbon cage is 400-800m 2 / g; And / or, the total pore volume of the nitrogen-doped nanocarbon cage is 0.9-1.5 cm 3 / g.
9. The method according to any one of claims 1 to 8, wherein: The nitrogen-doped nanocarbon cage has a double mesopore distribution peak, and the double mesopore distribution peaks correspond to a first most probable pore diameter and a second most probable pore diameter, respectively, the first most probable pore diameter is 3.5-4 nm, and the second most probable pore diameter is 6-9.5 nm; And / or, in the Raman curve of the nitrogen-doped nanocarbon cage, I D / I G The range is 0.2-1, preferably 0.3-0.
8.
10. The method according to any one of claims 1 to 9, wherein: In step (2), the temperature of the solid-liquid separation is 20-100°C, preferably 50-100°C.
Citation Information
Patent Citations
Method for purifying furandicarboxylic acid
CN103965146A
Method for refining furandicarboxylic acid
CN110713474A
Method for purifying and refining 2,5-furandicarboxylic acid
CN113121480A
Process for the preparation of a purified acid composition
CN107848998A
Carbon nano cage carrier-based metal monoatomic catalyst and preparation method thereof
CN109126857A